Peran Independensi, Pengalaman Kerja, Etika Profesional dan Gaya Kepemimpinan terhadap Kinerja Auditor - Syafira Dea Alfira; Binti Shofiatul Jannah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study discusses the influence of independence, work experience, professional ethics, and leadership style on auditor performance. The background of the study shows the importance of the role of auditors in ensuring transparent and reliable financial reports. Using a descriptive-based literature study method, this study processes secondary data from various journals. The results show that independence, work experience, and professional ethics have been proven to improve auditor performance so that they can also improve audit quality and public trust, while transformational leadership style encourages team motivation and collaboration. Research recommendations include strengthening independence policies, ongoing training, consistent application of professional ethics, and leadership that supports auditor development.